New Chinese entrepreneurs - Zhang, Wenxian (Henry Stewart Talks, 2013)
Entrepreneurship in emerging markets, Chinese economic reform, Entrepreneurial framework in China, Profile of Chinese entrepreneurs, Female entrepreneurship in China, Chinese diaspora, Entrepreneurial characteristics